Cost-effectiveness of biomarker-directed toripalimab plus chemotherapy for previously untreated extensive-stage small-cell lung-cancer in China - Shuo Kang; Shan Zhao; Xiaohui Wang; Zhenhua Pan (PLoS ONE, 2025)
Background With or without biomarker-directed toripalimab plus chemotherapy could bring significant clinical benefit and acceptable safety profile compared with chemotherapy as first-line treatment for patients with extensive-stage small-cell lung-cancer (ES-SCLC) were demonstrated in EXTENTORCH trial. However, its cost-effective remains uncleared. Objective The current analysis aimed to evaluate the economic value of intratumor heterogeneity (ITH) testing directed toripalimab plus chemotherapy as first-line treatment for patients with ES-SCLC from the Chinese health-care system perspective. Design A mathematical decision model-based cost-effectiveness analysis, Methods A pharmacoeconomic decision model was developed to simulate 3-week patients transition in 20-year time horizon to access the cost-effectiveness of three competing first-line treatments among ITH-testing directed toripalimab plus chemotherapy, toripalimab plus chemotherapy, and chemotherapy alone. Survival data were obtained from EXTENTORCH trial, cost and utility values were gathered from the dataset and published studies, annual discount rate of 5% was used for cost and utility values. Total cost, life-years (LYs), quality-adjusted life-years (QALYs), and incremental cost-effectiveness ratio (ICER) were the model outputs. One-way and probabilistic sensitivity analyses were conducted to estimate the robustness of the model results, Results In base-case analysis, compared with toripalimab plus chemotherapy and chemotherapy alone, ITH-testing directed therapy could bring additional 0.14 QALYs and 0.29 QALYs, with marginal costs of $3750.75 and $7778.18, resulting in the ICER of $27,353.27/QALY and $26,461.46/QALY, respectively, which lower than the Chinese willingness-to-pay (WTP) threshold. Sensitivity analyses demonstrated the model results were robust, probabilistic sensitivity analyses showed the probability of ITH-testing directed therapy could be considered cost-effective was 61%. Conclusions ITH-testing directed treatment was likely to be the most cost-effective first-line option compared with toripalimab plus chemotherapy and chemotherapy alone for patients with previously untreated ES-SCLC from the Chinese health-care system perspective.